A demographic analysis of breadwinner and domestic childcare roles in Australia's employment structure - Travaglione, Tony; Chang, Joshua (Taylor & Francis Australasia, 2012)
A relatively high level of part-time employment exists in Australia, with part-time workers having little incentive to move into full-time work due to a lack of work and family provisions in industrial agreements. This engenders the need to understand how the demographic structure of employment is shaped by such policy. This study seeks to investigate the breadwinner and childcare roles within Australia's employment structure by analysing employment status and relevant demographic variables using data from the 'Australia at Work' survey. We found that among households with dependent children, men dominated breadwinner roles, possibly to coutervail the partial employment of their female partners who were found to trade-off employment for child-caring roles within the household. This study shows how industrial agreements have influenced work and family roles in the employment structure, and serves as a basis for measuring the impact of recent policy reforms such as more flexible working arrangements for parents.